Strategi Partai Komunis Malaya Dalam Pergerakan Di Malaysia 1930-1968 - Samudra Eka Cipta; Wawan Darmawan (Lambung Mangkurat University, 2024)
The Communist Party of Malaya (PKM) employed a variety of strategies to disseminate its ideology among the general public. During the early 1920s, the communist movement utilized the